A LITERATURE STUDY : THE INFLUENCE OF LIFESTYLE ON FASHION PURCHASING DECISIONS - Putri, Amelia Pristian Syah; Darmawan, Didit (This journal is published by the Vocational School of Universitas Sebelas Maret., 2025)
Regeneration from era to era has a revolution that is quite significant and has a profound impact on aspects of life. Aspects of life have important factors, including how to interact and express oneself. This research study uses a literature study to determine the influence of lifestyle on purchasing decisions in the fashion industry. This research was conducted through qualitative methods sourced from journals and articles, which became primary data. The data collection technique in this study prioritizes primary data in the form of journals and articles. The primary data is collected from journals and articles because this research focuses on literature studies. The data obtained was then analyzed using coding techniques to make it easier for researchers to group relevant variables. This literature study review results shows that the processes show how consumers analyze various information and inputs before making a final decision. The lifestyle perspective is a person's model of living life, which is reflected in how they spend their time. Activities include work, hobbies, shopping, sports, and social interactions. In addition, a person's interests can include various aspects, such as food, fashion, family, and recreation, as well as views on oneself, social issues, business, and products. That’s is why it can be said that in a lifestyle has significant positive effect on the on fashion purchasing decisions.